Aberrant SOX9 expression mediated by protumour macrophages predicts poorer clinical outcomes in hepatoblastoma - Hiroki Hirao; Ahmad Adawy; Yukio Fujiwara; Daiki Yoshii; Cheng Pan; Lianbo Li; Hiromu Yano; Yoshihiko Kondo; Masaki Honda; Jia Han; Yao Liu; Sohsuke Yamada; et al. (The Journal of Pathology, 2026)
Abstract Tumour‐associated macrophages (TAMs) are known to promote tumour progression in many kinds of malignant tumour, including hepatoblastoma (HB). Based on previous studies, we suggested that TAM‐mediated sex‐determining region Y‐box 9 (SOX9) signal might enhance HB progression. The present study investigated the significance of the SOX9 signal in HB and examined the mechanisms underlying cell–cell interactions between tumour cells and TAMs. Co‐culture with human monocyte‐derived macrophages increased SOX9 expression in HB cell lines. Immunohistochemical analysis of HB samples revealed a positive correlation between SOX9 expression and TAM infiltration, and SOX9 expression was predominantly observed in the embryonal subtype. Increased SOX9 expression was associated with shorter 5‐year recurrence‐free and overall survival. Yes‐associated protein (YAP)/transcriptional co‐activator with PDZ‐binding motif (TAZ) signalling was found to be involved in macrophage‐induced SOX9 upregulation. The Wnt/β‐catenin pathway was also activated by co‐culture with macrophages and appeared to be upregulated by SOX9 expression. In summary, SOX9 was identified as a poor prognostic factor in HB, with expression enhanced by macrophage‐derived factors. The YAP/TAZ and Wnt/β‐catenin pathways are critical for cell–cell communication and are linked to SOX9 overexpression. © 2026 The Pathological Society of Great Britain and Ireland.